Mapping of Co-Creation Resources in Lekki Conservation Centre and Omu Resort Lagos, Nigeria - Tunde-Ajayi, Olalekan; Adetola, Bukola Omotomilola (Journal of Tourism Management Research, 2020)
This study categorized and mapped the value co-creation resources at Lekki Conservation Centre and Omu Resort Lagos, Nigeria, for effective marketing, projection of the spatial distribution of tourism products, successful service delivery and efficient customer satisfaction. Field survey was used to identify the tourism resources and facilities supporting value co-creation among the tourists. Spatial data of value co-creation facilities’ locations were collected using hand-held Global Positioning System and their photographs were subsequently captured with a digital camera. These data were uploaded into Quantum GIS software for analysis. The map of co-creation resources was produced using GIS overlay, including geo-tagging each of the facilities location with its photograph to generate the co-creation resource map. A total of 21 and 11 recreational resources were identified at Omu Resort and LCC respectively, out of which 7 were categorized as co-creation facilities in each of the sites. Research concluded that more facilities promoting value co-creation should be added at tourism sites for destinations to have a competitive edge in the tourism market since tourists now enjoy being in control of how values are created for themselves through active participation and interaction with other tourists.